Efeitos de uma intervenção comportamental sobre o comportamento de chute no gol" em jogadores de futebol em formação - Abuchacra, Marcelo Corrêa (2016)
The present study aims to investigate the influence of a conditioned reinforcement on the performance of base categories soccer players at the behavior of completion of the goal. To measure the accuracy of the kicks, the goal will be divided into four targets (lower right, lower left, upper right and upper left), according to the Battery of tests Mor-Christian. . Investigation of the performance of the participants will be held through a multiple base line design, consisting of a baseline and a subsequent step of conditioned reinforcement. At the end of the sections in the second phase, the participants can exchange the points accumulated on the task for money. Data obtained by each participant in each stage of the research will be analyzed and compared, in order to check the influence of the conditioned reinforcement on the performance of participants regarding the amount of hits to established targets